Advanced electromagnetic modeling of large-scale high-temperature superconductor systems based on H and T-A formulations. (23rd February 2021) - Berrospe-Juarez, Edgar; Trillaud, Frederic; Zermeño, Víctor M R; Grilli, Francesco
Abstract: The development of the high-temperature superconductors (HTS) has allowed the emergence of diverse superconductor devices. Some of these devices, like wind power generators and high-field magnets, are classified as large-scale HTS systems, because they are made of several hundreds or thousands of turns of conductors. The electromagnetic analysis of such systems cannot be addressed by means of the available analytical models. The finite-element method has been extensively used to solve the H formulation of the Maxwell's equations, thus far with great success. Nevertheless, its application to large scale HTS systems is still hindered by excessive computational load. The recently proposed T-A formulation has allowed building more efficient models for systems made of HTS tapes. Both formulations have been successfully applied in conjunction with the homogenization and multi-scaling methods, these advanced methods allow reducing the required computational resources. A new advanced method, called densification, is proposed here. The most important contribution of this article is the comprehensive comparison of the strategies emerged from the combined use of the two formulations and the three advanced methods.